Research on open source software intended to promote its usage in education - Dagiene, Valentina (2006)
The paper deals with the use of open source software in education. Open source software is used more and more all over the world. Linux, Mozilla, MySQL, OpenOffice.org etc. are very well-known packages. A lot of open source programs are developed especially for educational purposes: virtual learning environments, editors, simulators, microworlds, subject-based learning applications, etc. The main problem of this field is to involve educators and policy makers to disseminate effectively information about open source, and to bring students and teachers together for improving open code. The investigations on open source are being fulfilled in a few Lithuanian institutions. The main objectives are to validate the economic and pedagogical utility of open source software in schools.